SQUARE-IT: a proposed approach to square the identified research problem in the literature with the objectives, the appropriate clinical research question, and the research hypothesis - Martin Alfuth; Jonas Klemp; Annette Schmidt; Lukas Streese; Nikolai Ramadanov; Robert Prill (BMC Medical Research Methodology)
Abstract The purpose of this article is to design and introduce the SQUARE-IT approach to help scientists and clinicians in research to align important research problems with the objectives, the appropriate clinical research questions to be answered, and the research hypotheses to be investigated in medical and therapeutic specialties. Research ideas can be generated primarily through simple methods such as brainstorming and mind mapping. However, transforming ideas into a valid research question is not as easy as it may seem, as the mere presence of an idea does not guarantee that the researcher has already uncovered existing knowledge on a particular topic or identified the actual research problem. Therefore, the SQUARE-IT items are developed, described, and critically discussed with reference to the scientific literature. They ask whether the identified research problem is ‘Specific’, ‘Quantifiable’, ‘Usable’, ‘Accurate’, ‘Restricted’, ‘Eligible’, ‘Investigable’, and ‘Timely’. Before formulating the focused clinical question, SQUARE-IT can be used as a preparatory step to enable researchers to organize the relevant information that has been explored to date and to assess whether additional information is needed, thereby identifying current research gaps. In addition, it should facilitate the effectiveness and efficiency of evidence-based practice to ensure high quality patient care. Using SQUARE-IT as a framework, further elaboration of the approach and addition of other aspects are warranted to advance the discussion and improve methods of evidence-based practice in medical and therapeutic specialties for quality improvement of patient care.